2014
DOI: 10.1159/000365578
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ureteroscopy with Holmium Laser Lithotripsy: A New Choice for Intrarenal Stone Patients

Abstract: Objective: To evaluate the efficiency and safety of flexible ureteroscopy (FURS) and holmium lithotripsy for intrarenal stones and to stratify the efficiency and safety by stone burdens of ≤20, 20-40, and ≥40 mm. Methods: Five hundred eighty-two patients with intrarenal stones were treated with FURS and holmium lithotripsy at a single department from August 2008 to October 2013. Stone size was evaluated by calculating the cumulative stone diameter of all intrarenal stones, and stone-free status was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…However, the mean operating time was significantly longer in the microperc group (130 vs. 98 min, p = 0.002). Xu et al [23] found that fURS using intrarenal holmium laser lithotripsy may serve as an alternative to mini percutaneous procedures even in larger kidney stones (>2 cm diameter). The estimated pSFR was 65% in their study and increased to 89% 6 months after the first surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean operating time was significantly longer in the microperc group (130 vs. 98 min, p = 0.002). Xu et al [23] found that fURS using intrarenal holmium laser lithotripsy may serve as an alternative to mini percutaneous procedures even in larger kidney stones (>2 cm diameter). The estimated pSFR was 65% in their study and increased to 89% 6 months after the first surgery.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with PCNL, F-URS was widely recognized for its faster post-operative recovery (Xu et al, 2015;Miernik et al, 2012). In our study, the mean post-operative duration of SMP was also longer than the F-RUS, as SMP still made certain wounds to the target kidney and the patients needed more recovery time in bed.…”
Section: Discussionmentioning
confidence: 55%
“…The application of F-URS has been widespread for the treatment of intra-renal stones due to its many recognized advantages, including: minimal invasiveness, less blood loss and fewer post-operative hospital stays (Doizi et al, 2015;Xu et al, 2015;Wang et al, 2018). However, the high cost of F-URS including operation-related cost for patients and the original purchasing cost, the reprocessing cost and repair fees of the flexible ureteroscope for healthcare institutions limit the use of this procedure worldwide (Schoenthaler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasery mają szczególnie istotne znaczenie w leczeniu kamicy układu moczowego. Dzięki zastosowaniu giętkich endoskopów możliwy jest dostęp do całego górnego odcinka górnych dróg moczowych, zarówno moczowodów, jak i układu kielichowo-miedniczkowego nerki [17]. Miniaturyzacja i elastyczność włókien optycznych powoduje, że lasery są powszechnie stosowane w zabiegach endourologicznych.…”
Section: Leczenie Kamicy Układu Moczowegounclassified